KEBUTUHAN PENDIDIKAN KETERAMPILAN BAGI PENCARI KERJA DI KECAMATAN MAJE KABUPATEN KAUR PROVINSI BENGKULU - Muchtar, Sazili (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2010)
This study aimed to identify the type of skills required of job seekers in the District Maje Kaur Bengkulu Regency. Study sample was 100 young men and women job seekers of 5 (five) villages in the district Maje Kaur Bengkulu Regency. Techniques used in sampling is purposive sampling Stratafied. Data analysis was performed with descriptive percentages. The results of data collection and tabulation showed that of 100 respondents, a junior high school educated (27 persons), senior (46 people) and University Yinggi (27 people). Skills needs of job seekers in the District table is shown: (35 people) requires skills workshop, (18 people) carpentry, (17 people) culinary skills, (11 people) cosmetology skills, (9 people) require computer skills and (9 people ) requires skill electrical installers.